REHABILITATING THE HOARD: THE SOCIAL DYNAMICS OF UNBANKING IN AFRICA AND BEYOND - Peebles, Gustav (Africa (London. 1928), 2014)
If a thriving capitalist economy relies on the innumerable small deposits of savings that local people place in banks, then ‘unbanking’ represents a threat to just such an economy. And yet, across the globe, billions remain outside the formal banking sector, thereby reducing the ability of formal banks to set these savings in motion. This unbanking has been the subject of many reports and studies by economists, corporations and non-profit organizations, but unbanking never seems to diminish. Indeed, by all accounts, it continues to thrive. In order to offer an alternative explanation for this phenomenon, the author revives an important, age-old distinction between hoarding and saving, while also providing an anthropological survey of alternative modes of saving in Africa. In so doing, the author argues that the critics of unbanking may be ignoring the ways in which banking and unbanking are tied up with subject formation. Dès lors qu'une économie capitaliste florissante est tributaire de l'argent que déposent dans les banques d'innombrables petits épargnants locaux, la « non-bancarisation » représente une menace pour cette économie. Et pourtant, il existe dans le monde des milliards de personnes qui restent en dehors du secteur bancaire formel, réduisant par là-même la capacité des banques formelles à mobiliser cette épargne. Malgré les nombreux rapports et études produits par les économistes, les entreprises et les organisations à but non lucratif au sujet de la non-bancarisation, ce phénomène semble ne jamais décroître. Tout porte à croire même qu'il continue de se développer. Afin d'offrir une autre explication de ce phénomène, l'auteur reprend une très ancienne et importante distinction entre la thésaurisation et l’épargne, tout en offrant une étude anthropologique des différents modes d’épargne en Afrique. Ce faisant, l'auteur suggère que la critique de la non-bancarisation ignore peut-être les manières dont la bancarisation et la non-bancarisation sont liées à la formation du sujet.